A simple LC-MS/MS method for pharmacokinetic study of carvedilol and 4/-hydroxyphenyl carvedilol at a low dose - Wanna Eiamart; Nantaporn Prompila; Yaowatree Jumroen; Nonlanee Sayankuldilok; Pajaree Chariyavilaskul; Supeecha Wittayalertpanya (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: The study was aimed at validating a simple, rapid, and low-cost LC-MS/MS method for carvedilol and 4/-hydroxyphenyl carvedilol assay in human plasma. The validated method was applied to investigate the pharmacokinetics after a low dose of 6.25 mg. carvedilol. Experimental approach: In this study, the plasma was extracted by liquid-liquid extraction and evaporated the organic layer to dryness, then both analytes in the residue were reconstituted and detected by LC- MS/MS. The method was validated following the guideline on bioanalytical method validation. Thirty-one healthy volunteers participated in the pharmacokinetic study. After 10 h of fasting, each volunteer received one tablet of 6.25 mg carvedilol orally. Blood samples were collected at 16 prescheduled time points. The plasma samples were analyzed for pharmacokinetics. Findings/Results: The method was linear over a range of 0.050-50.049 ng/mL for carvedilol and 0.050-10.017 ng/mL for 4/-hydroxyphenyl carvedilol. Crucial validated results reached the requirements of selectivity, accuracy, precision, and stability. Pharmacokinetics of carvedilol and 4/-hydroxyphenyl carvedilol were evaluated which showed Cmax at 21.26 ± 9.23 and 2.42 ± 2.07 ng/mL; AUC0-t 66.95 ± 29.45 and 5.93 ± 3.51 ng.h/mL; AUC0-inf 68.54 ± 30.11 and 6.78 ± 3.49 ng.h/mL; and T1/2 6.30 ± 1.95 and 6.31 ± 6.45 h, respectively. Conclusion and implications: The validated method was able to detect and quantify both analytes in plasma samples and can be applied to the pharmacokinetic study of carvedilol and 4/-hydroxyphenyl carvedilol after receiving carvedilol at 6.25 mg orally.